2020
DOI: 10.1007/s10439-020-02627-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laboratory and On-Field Performance of American Football Helmets

Abstract: The relationship between laboratory and on-field performance of football helmets was assessed for 31 football helmet models selected from those worn by players in the 2015-2019 National Football League (NFL) seasons. Linear impactor tests were conducted with helmets placed on an instrumented Hybrid III head and neck assembly mounted on a sliding table. Based on impacts to each helmet at six impact locations and three velocities, a helmet performance score (HPS) was calculated using a linear combination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
(59 reference statements)
1
23
0
Order By: Relevance
“…Both producers and NOC-SAE indicate that football helmets may not fully protect the player. Other research communities have made similar conclusions in the literature [58,[84][85][86][87][88][89][90][91][92].…”
Section: Discussionsupporting
confidence: 62%
“…Both producers and NOC-SAE indicate that football helmets may not fully protect the player. Other research communities have made similar conclusions in the literature [58,[84][85][86][87][88][89][90][91][92].…”
Section: Discussionsupporting
confidence: 62%
“…Changes to the kickoff, which eliminated running starts and wedge blocks, were piloted and subsequently implemented. Extensive laboratory testing on commercially available helmets, 1 subsequent distribution of results to players and staff in a poster format, and instantiation of rules mandating helmet transitions out of poorly performing helmets led to movement of players into higher performing helmets. These efforts led to 99% of players wearing better performing helmets by the 2019 season.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study further confirmed a positive correlation between impact testing and real-world performance of helmets, whereby helmets which exhibited reduced headform accelerations in laboratory tests were also associated with lower concussion rates. 1 However, predicting an absolute concussion probability depends on the accuracy of injury risk curves that have been reconstructed from a limited number of real-world injury data to estimate brain tolerance limits. Moreover, these injury risk curves are highly non-linear, for which reason a relatively small difference in peak rotational velocity can translate into a large difference in injury probability.…”
Section: Discussionmentioning
confidence: 99%